Validation of the Early Childhood Affective Ability and Behavior Questionnaire on Self-Protection from Suspicious Touches - Esa Risi Suazini, Esa Risi Suazini; Rosita Alvia, Rosita Alvia (Karsa Husada Health Institute Garut, 2025)
Victims of sexual violence are predominantly children. This is due to a lack of understanding of the boundaries of